(untitled) (Research, Society and Development, 2020)
Obesity is seen as a major public health problem and it is characterized by the excess of fat tissue in the body. This tissue is subdivided into white adipose tissue and brown adipose tissue. Studies have shown that the adipose tissue is responsible for the release of signaling substances, called adipokines, which have several functions and their immunological role is the most important attribution. This paper aims to address the characteristics of obesity and its relationship with the immune system. This condition came to be seen as an inflammatory disease, since pro-inflammatory and anti-inflammatory adipokines are at altered levels. This study is a bibliographic review, with a qualitative approach, of an exploratory type. The results obtained in this bibliographic research confirm that resistin and leptin, which are pro-inflammatory adipokines, are in high levels in patients with obesity, while adiponectin, Interleukin-4 and Interleukin-10, which are anti-inflammatory adipokines, are in lower levels in these patients when compared to patients with no obesity. The study of the molecules involved in the pathophysiology of obesity is extremely important, since this is an increasingly common condition in the world, and it leads to several losses, including the development of inflammatory and chronic diseases.